METHODOLOGICAL COMPONENT OF FORMING THE MARKET OF GOAT PRODUCTS IN UKRAINE - Vdovenko, Nataliia; Hryshchenko, Nataliia; Marchenko, Natalia (Науковий вісник Полісся, 2017)
Urgency of the research. The article describes the main macroeconomic indicators of development of agricultural sector of the economy. The results of the state prediction of economic and social development of Ukraine are considered. The dynamics of GDP, GVA in agriculture, current state of crop and livestock production, dynamics of food production, and the structure of export-import of agricultural products, the using of material and technical resources for agricultural production are analyzed. The perspectives of agricultural production development are considered. Target setting. The article aims at studying the problems of goat industry functioning. It promotes the development of methodological foundations for solving the problem of replacing import products at a domestic market with domestic goat products and providing the population with affordable food products. Actual scientific researches and issues analysis. Many leading scientists and economists elaborate the issue of focuses of regulating the areas of an agrarian sector of economy and the study of peculiarities of structuring the production of agricultural products. Among them there are S. M. Kvasha, V. Ye. Andriyevsky, A. D. Dibrova, N. M. Korobova, S. M. Chystov, A.-M. Slaughter, J. E. Stiglitz and many others authors. Uninvestigated parts of general matters defining. The problem that hinders the development of goat industry as an area is its separation from sheep industry. Thus there are opportunities which should be used to provide the population with appropriate food. The research objective is to identify a methodological component of forming the goat products market in Ukraine taking into account modern global components of economic development of an agrarian sector. The statement of basic materials. The adaptation of economic processes in Ukraine to the chosen European integration focus has stimulated the reforming of the focus of development of livestock products production. In terms of general state of economy of Ukraine, objective regional and industrial problems the modern state of goat industry is suffering the state of the lack of industrial complexes when productive resources are concentrated in people’s households. Conclusions. The development of an agrarian market requires the improvement of standard and legal framework for goat industry in Ukraine. The increase of the offer for goat products is hindered by a poor mechanism of state regulating the development of this area.